2002
DOI: 10.1016/s0074-7696(02)17015-x
|View full text |Cite
|
Sign up to set email alerts
|

Photoreceptor renewal: A role for peripherin/rds

Abstract: Visual transduction begins with the detection of light within the photoreceptor cell layer of the retina. Within this layer, specialized cells, termed rods and cones, contain the proteins responsible for light capture and its transduction to nerve impulses. The phototransductive proteins reside within an outer segment region that is connected to an inner segment by a thin stalk rich in cytoskeletal elements. A unique property of the outer segments is the presence of an elaborate intracellular membrane system t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 183 publications
1
45
0
2
Order By: Relevance
“…The post-Golgi vesicles that transport rhodopsin have a unique phospholipid composition, containing phosphatidylcholine and phosphatidylethanolamine with docosahexaenoyl (DHA) acyl chains [64]. Modification of phospholipid biosynthesis affected fusion and budding of the transport membranes differently [65] Furthermore, the organization of cholesterol within the disk membranes may also be determined prior to the formation of a new disk [66].…”
Section: Cholesterol Distribution Among Ros Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…The post-Golgi vesicles that transport rhodopsin have a unique phospholipid composition, containing phosphatidylcholine and phosphatidylethanolamine with docosahexaenoyl (DHA) acyl chains [64]. Modification of phospholipid biosynthesis affected fusion and budding of the transport membranes differently [65] Furthermore, the organization of cholesterol within the disk membranes may also be determined prior to the formation of a new disk [66].…”
Section: Cholesterol Distribution Among Ros Membranesmentioning
confidence: 99%
“…These studies have provided in vitro evidence that the product of the RDS gene, peripherin/rds (a.k.a. peripherin-2) functions as a photoreceptor specific membrane fusion protein [125,126] and for review [66].…”
Section: Organization Of Cholesterol In Disk Membranesmentioning
confidence: 99%
“…Periph-erin/rds participates in the maintenance of normal ROS disk membrane structure and in disk morphogenesis and shedding (Ref. 15 and references therein) and acts as a photoreceptorspecific fusion protein (16,17).…”
mentioning
confidence: 99%
“…Both of these processes requires tightly regulated membrane fusion events, in the delivery of new membraneous material from the IS (Deretic and Papermaster 1991;Deretic and Papermaster 1993;Deretic and Papermaster 1995;Chuang, Vega et al 2004), for disk closure during morphogenesis (Steinberg, Fisher et al 1980;BoeszeBattaglia and Goldberg 2002) and in disk packet formation and shedding (Boesze-Battaglia and Goldberg 2002;Chen, Yunhai et al 2002). Previous studies in our laboratory have suggested that disks at the apical tip of the OS fuse spontaneously to delineate a packet of disks (Boesze-Battaglia 1997) and that the tetraspanin protein, peripherin/rds (P/rds a.k.a.…”
Section: Introductionmentioning
confidence: 99%